Como vinimos al quinto mundo = How we came to the fifth world - Rohmer, Harriet; Anchondo, Mary; Carrillo de Lopez, Graciela (San Francisco : Children's Book Press, 1976)
An Aztec myth recounting the creation and destruction of the world by the deities of the four great elements.
"Mexico".
English and Spanish.
Keywords: Aztecs -- Folklore; Spanish language -- Readers -- Folklore; Indians of Mexico -- Folklore; Aztecs -- Folklore; Indians of Mexico -- Folklore; Spanish language materials -- Bilingual